HUBUNGAN ANTARA BERAT BADAN LAHIR BAYIÂ DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RUMAH SAKIT ISLAM SAKINAH KABUPATEN MOJOKERTO - Novrelia J, Sheila; Maâ€™rifah, Asirotul (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Indonesias commitment to achieve the MDGs reflects the states commitment to the welfare its people while contributing to the welfare of the world community. The main causes of the death in the first week of life was complications during pregnancy and childbirth as asphyxia. Risk factors associated with the occurrence of asphyxia one of which was LBW. This study aims to determine the relationship between birth weight with neonatal asphyxia events in Sakinah Mojokerto 2014. The design of the study was an analytic cross sectional correlation. The population in this study were all newborns in Sakinah Islamic Hospital Mojokerto in July-August 2014 as many as 41 babies. The sampling technique used was consecutive sampling. Number of samples are 30. The results showed that the majority of babies are born with normal birth weight is 66.7%, that most respondents did not got birth asphyxia, as many as 63.3%. Results of analysis using Spearmans rho test results obtained ρ value (0.001) <α (0.05) which means that H0is rejected and H1is accepted, it means there is a relationship between birth weight infants with neonatal asphyxia at birth mother in Sakinah Islamic Hospital Mojokerto in 2014.More normal birth weight of the newborn, more possible for baby not to be asphyxia, because low birth weight baby has not have mature body function thus baby can not breath spontaneously and get asphyxia.Keywords: birth weight, asphyxia, newborn